Evaluation of Effect of Different Crop Types On Soil Water Erosion: Case Study of the Myjava Hill Land, Slovakia. Issue 2 (February 2019) - Nemetova, Zuzana; Kohnova, Silvia; Foldes, Gabriel
Abstract: The main objective of the study is to model and evaluate the effect of different types of crops on soil water erosion by using the physically-based EROSION-3D model. The EROSION-3D model is based on physical principles and simulates surface runoff, erosion, the deposition of material, and the detachment of soil particles for a single rainfall event. The erosion model was applied to a small catchment of Svacenicky Creek (6.86 km 2 ), which is situated in the Myjava Hill Land in the western part of Slovakia; it is known for its quick runoff responses and related erosion processes. The parts most prone to erosion processes are located in the northern part of the Svacenicky Creek catchment on slopes with a more than 20% angle. Three crop types (winter wheat, silage corn and sugar beets) were chosen in consideration of their growing periods in order to assess the dynamic character of the erosion processes, especially during the growing period of each single crop. The modelling was performed for design rainfall events that were derived separately for each month and which were inputs to the model according to the growing period of the selected crops; six scenarios of the initial soil moisture in a range of 10-40% were designed. The results demonstrated the differences between the erosive effects of the crops selected during their growing periods. Finally, the results were statistically evaluated to determine the differences between the various scenarios of the initial moisture, different rainfall events, and selected crop types.